2007
DOI: 10.1007/s10750-006-0557-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a retrofitted downstream fish bypass system for wild Atlantic salmon (Salmo salar) smolts and kelts at a hydroelectric facility on the Exploits River, Newfoundland, Canada

Abstract: In 2002 and 2003, the Bishops Falls hydroelectric generating facility on the Exploits River, insular Newfoundland, Canada, underwent extensive refurbishing including replacement of turbines and installation of a 'retrofitted' bypass and fish handling system. The effectiveness of this new bypass system has been assessed during the annual downstream run of wild Atlantic salmon smolt and kelt in smolt were radio tagged and released between June 9 and July 2, in the forebay of the hydro plant (19 releases) and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…No diel control was apparent. The pattern of diel control on kelt seaward migration had been less consistent throughout the literature (Bendall et al 2005 andScruton et al 2007 identifying nocturnal migration; Östergren & Rivinoja 2008 identifying daytime migration). We hypothesize that the lack of a tendency for nocturnal migration is suggestive of low predation pressure on the kelts from piscivorous fish and birds: avoidance of predation should cause a preference for movement under the cover of darkness (Bendall et al 2005).…”
Section: Factors Controlling Coastal Zone Migrationmentioning
confidence: 97%
See 1 more Smart Citation
“…No diel control was apparent. The pattern of diel control on kelt seaward migration had been less consistent throughout the literature (Bendall et al 2005 andScruton et al 2007 identifying nocturnal migration; Östergren & Rivinoja 2008 identifying daytime migration). We hypothesize that the lack of a tendency for nocturnal migration is suggestive of low predation pressure on the kelts from piscivorous fish and birds: avoidance of predation should cause a preference for movement under the cover of darkness (Bendall et al 2005).…”
Section: Factors Controlling Coastal Zone Migrationmentioning
confidence: 97%
“…Some authors have identified kelt migration as being nocturnal (Bendall et al 2005 for sea trout Salmo trutta kelts), while Östergren & Rivinoja (2008) found that sea trout migration tended to occur during daytime. In the case of Atlantic salmon kelts, Scruton et al (2007) reported nocturnal migration, whereas no diurnal patterns were observed by Hubley et al (2008). Bendall et al (2005) found that sea trout migration tends to occur on the ebb tide.…”
Section: Introductionmentioning
confidence: 99%
“…Telemetry applications for fish range from monitoring fine spatial movements and habitat preferences to monitoring large-scale migratory patterns (Skalski 1998;Scruton et al 2007). Within rivers and basins, telemetry has proven to be an essential tool for assessing fish survival and movement patterns (Jepsen et al 1998;Skalski 1998;Plumb et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Telemetry applications for fish range from monitoring fine spatial movements and habitat preferences to monitoring large-scale migratory patterns (Skalski 1998;Scruton et al 2007). In the Columbia River, scientists have identified acoustic telemetry as being an essential technology for observing the behavior and estimating the survival of juvenile salmonids passing through the side channels and the main-stem FCRPS (Faber et al 2001;McComas et al 2005;Ploskey et al 2007Ploskey et al , 2008Clemens et al 2009).…”
Section: A1 Backgroundmentioning
confidence: 99%